Accounting in a ‘New’ History: A Disciplinary Power and Knowledge of Accounting - Sukoharsono, Eko Ganis (The International Journal of Accounting and Business Society, 1998)
There has been a growing number of research studies in accounting history challenging accounting researchers to re-examine extant explanations for the sustained emergence of accounting (eg., Hopwood [1985], Loft [1986], Miller and O'leary [1987], Miller, et al [1991], Stewart [1992], Hopper and Macintosh [1993]. and Tyson [1993]). These studies have criticised some traditional histories which are "ahistoricaI" and "antiquarian" in nature. They have questioned the methodological stance in exploring the history of accounting. This paper explores an alternative way researching phenomena in accounting under a Foucouldian view, a disciplinary power and knowledge. With this view, it would open accounting researchers‘ minds to being aware of the broader context of accounting in social phenomena. Accounting is no longer seen as only a technical and neutral apparatus. Accounting as a disciplinary power and knowledge appears not as a single dimensional aspect, but as a complexity of social, political, and economic phenomena in society.